2020
DOI: 10.1186/s41983-020-0160-1
|View full text |Cite
|
Sign up to set email alerts
|

Anti-GAD-associated limbic encephalitis: an unusual clinical manifestation from northwest of Ireland

Abstract: We report an unusual manifestation of anti-GAD-associated limbic encephalitis in a 59-year-old man following pacemaker insertion for cardiac pauses. Clinically, the association of anti-GAD antibody with limbic encephalitis is rare. He presented with a complex constellation of symptoms, posing a diagnostic and therapeutic challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Despite the two years follow -up the results were normal. This experience may suggest that anti-Gad might not always be neoplastic in children, but This paper supports that GAD antibodies could play a pathogenic role in neurological disease [1,6,7].…”
Section: Discussionmentioning
confidence: 51%
“…Despite the two years follow -up the results were normal. This experience may suggest that anti-Gad might not always be neoplastic in children, but This paper supports that GAD antibodies could play a pathogenic role in neurological disease [1,6,7].…”
Section: Discussionmentioning
confidence: 51%
“…GAD antibodies are most frequently found in GABAergic neurons and pancreatic islet cells, with the associated neurological syndromes, such as stiff-person syndrome, limbic encephalitis, and cerebellar ataxia, thought to arise secondary to the loss of inhibitory neurotransmission from GABA [ 61 ]. A recent review of 58 patients with anti-GAD associated encephalitis showed that the most common manifestations were seizures (97%), impaired memory (59%), cognitive impairment (40%), psychiatric symptoms, mainly related to depression or personality change (28%), and status epilepticus (24%) [ 62 ].…”
Section: Reviewmentioning
confidence: 99%
“…• BUT with anti-GAD antibodies -common symptoms are seizures (97%), memory impairment (59%), cognitive impairment (40%), psychiatric symptoms, mainly depression or personality changes (28%), and epileptic (24%) [19]. A characteristic symptom of this disease is Stiff-person syndrome.…”
mentioning
confidence: 99%